Analisa Performa Website Badan Penanggulangan Bencana Daerah (BPBD) Provinsi Sumatera Selatan menggunakan Automated Software Testing GTmetrix - Ramadhan, Moch Rizky Zulian; Mukti, Aan Restu; Atmojo, Toni Tri (Journal of Electrical Power Control and Automation (JEPCA), 2024)
Websites are an important communication medium for disseminating information openly and widely to all corners of the world. Websites are very important as a supporting facility for information and communication needs. A good website is a website that has fast access speed. Therefore the aim of this research is to analyze the website loading speed performance of the South Sumatra Regional Disaster Management Agency (BPBD) using GTmetrix. GTmetrix is a Google product designed to measure the performance of a website with results in the form of a page speed score and structure score in percent. GTmetrix will later provide information about parts of the website that have poor scores and provide solutions to improve the website.